Millimeter-wave profiled corrugated horns for the quad cosmic background polarization experiment - Murphy, J. A.; Gleeson, E.; Cahill, G.; Lanigan, W.; O'Sullivan, C.; Cartwright, E.; Church, S. E.; Hinderks, J.; Kirby, E.; Thompson, K.; Rusholme, B.; Gear, Walter Kieran; et al. (International Journal of Infrared and Millimeter Waves, 2005)
In this paper we report on the design and validation process for the profiled corrugated horn antennas, which feed the bolometer array of a cosmology experiment known as QUaD located at the South Pole. This is a cosmic background radiation polarization project, which demands precise knowledge and control of the optical coupling to the signal in order to map the feeble E- and B-polarization mode structure. The system will operate in two millimeter wavelength bands at 100 and 150 GHz. The imaging horn array collects the incoming signal via on-axis front-end optics and a Cassegrain telescope, with a cold stop in front of the array to terminate side-lobe structure at an edge taper of –20dB. The corrugated horn design process was undertaken using in-house analytical software tools, based on modal scattering, specially developed for millimeter -wave profiled horn antennas. An important part of the instrument development was the validation of the horn design, in particular to verify low edge taper levels and the required well-defined band edges. Suitable feed horn designs were measured and were found to be in excellent agreement with theoretical predictions.